Comprehensive analysis of differences in N6-methyladenosine RNA methylomes in Helicobacter pylori infection - Li, Huan; Lin, Jiahui; Cheng, Sha; Chi, Jingshu; Luo, Ju; Tang, Yu; Zhao, Wenfang; Shu, Yufeng; Liu, Xiaoming; Xu, Canxia (Frontiers in Cell and Developmental Biology, 2023)
Background:Helicobacter pylori (H.pylori) infection is an important factor in the occurrence of human gastric diseases, but its pathogenic mechanism is not clear. N6-methyladenosine (m6A) is the most prevalent reversible methylation modification in mammalian RNA and it plays a crucial role in controlling many biological processes. However, there are no studies reported that whether H. pylori infection impacts the m6A methylation of stomach. In this study, we measured the overall level changes of m6A methylation of RNA under H. pylori infection through in vitro and in vivo experiment. Methods: The total quantity of m6A was quantified in gastric tissues of clinical patients and C57 mice with H. pylori infection, as well as acute infection model [H. pylori and GES-1 cells were cocultured for 48 h at a multiplicity of infection (MOI) from of 10:1 to 50:1]. Furthermore, we performed m6A methylation sequencing and RNA-sequencing on the cell model and RNA-sequencing on animal model. Results: Quantitative detection of RNA methylation showed that H. pylori infection group had higher m6A modification level. M6A methylation sequencing identified 2,107 significantly changed m6A methylation peaks, including 1,565 upregulated peaks and 542 downregulated peaks. A total of 2,487 mRNA was upregulated and 1,029 mRNA was downregulated. According to the comprehensive analysis of MeRIP-seq and RNA-seq, we identified 200 hypermethylation and upregulation, 129 hypermethylation but downregulation, 19 hypomethylation and downregulation and 106 hypomethylation but upregulation genes. The GO and KEGG pathway analysis of these differential methylation and regulatory genes revealed a wide range of biological functions. Moreover, combining with mice RNA-seq results, qRT- PCR showed that m6A regulators, METTL3, WTAP, FTO and ALKBH5, has significant difference; Two key genes, PTPN14 and ADAMTS1, had significant difference by qRT- PCR. Conclusion: These findings provide a basis for further investigation of the role of m6A methylation modification in H. pylori-associated gastritis.